Validity of the modified shuttle walk test to assess cardiorespiratory fitness after exercise intervention in overweight/obese adults with primary hypertension - Borja Jurio-Iriarte; Peter H. Brubaker; Ilargi Gorostegi-Anduaga; Pablo Corres; Aitor Martinez Aguirre-Betolaza; Sara Maldonado-Martin (Clinical and Experimental Hypertension, 2019)
The study aimed to assess whether the Modified Shuttle Walk Test (MSWT) can detect changes in cardiorespiratory fitness (CRF) in overweight/obese people with hypertension (HTN) after an exercise intervention evaluating the equation presented in the previous research by Jurio-Iriarte et al. Participants (N= 248) performed a peak cardiorespiratory exercise test (CPET) and MSWT before and after 16-weeks of different types of aerobic exercise intervention. The formula of Jurio-Iriarte et al. was used to predict peak oxygen uptake (V̇O2peak). The correlation between measured and predicted V̇O2peak was strong (r= 0.76, P< 0.001) with a standard error of estimate (SEE) of 4.9 mL·kg−1·min−1; SEE%= 17%. The intraclass correlation coefficient indicates a moderate level of association and agreement (ICC= 0.69; 95% CI 0.34–0.82; P< 0.001) between the measured and predicted V̇O2peak. When analyzing obese participants alone (N= 128), MSWT equation was more accurate compared to the whole sample (ICC= 0.76; 95% CI 0.52–0.87). The relationship between the change of measured and predicted V̇O2peak at follow-up was weak (r= 0.42, P< 0.001) with a 31% SEE, and a low level of association and agreement (ICC= 0.31; 95% CI 0.06–0.49; P< 0.001). In conclusion, although MSWT does not accurately predict CRF in people with HTN after exercise intervention and questions its validity, the new equation may have practical application to estimate V̇O2peak for obese people with HTN when CPET is not available. Abbreviations: AC: Attention Control; BM: Body Mass; BP: Blood Pressure; CI: Confidence Interval; CRF: Cardiorespiratory Fitness; CPET: Cardiopulmonary Exercise Test; HTN: Primary Hypertension; HR: Heart Rate; HV-HIIT: High-Volume and High-Intensity Interval Training; ICC: Intraclass Correlation Coefficient; LV-HIIT: Low-Volume and High-Intensity Interval Training; MICT: Moderate-intensity continuous training; MSWT: Modified Shuttle Walk Test; SD: Standard Deviation; SEE: Standard Error of Estimate; V̇O2peak: Peak Oxygen Uptake.